Film Usage Strategies and the Elderly Mood States - Carmo, Elisangela Gisele do [UNESP]; Costa, Jose Luiz Riani [UNESP]; Schwartz, Gisele Maria [UNESP] (Neuropsicologia Cl, 2022)
This qualitative study aims to demonstrate, through a systematic literature review, the strategies for using films and their impact on the mood of elderly people. Therefore, searches were carried out in indexed databases in areas of knowledge related to the theme, using the guidelines of the Prism method. A total of 637 articles were found, and, after the selection step by title, abstract and full reading, there were 30 eligible studies. The results of the studies demonstrate that movies induce and produce numerous emotional responses in the elderly, contributing to the activation of brain connections, in order to define emotions based on such stimuli. This type of intervention suggests a viable and easily accessible alternative providing multiple benefits to the elderly in different instances.
Keywords: Movies; Mood states; Elderly